Evolution of acceptor stem tRNA recognition by class II prolyl-tRNA synthetase - An, Songon (Oxford University Press, 2008)
Aminoacyl-tRNA synthetases (AARS) are an essential family of enzymes that catalyze the attachment of amino acids to specific tRNAs during translation. Previously, we showed that base-specific recognition of the tRNA(Pro) acceptor stem is critical for recognition by Escherichia coli prolyl-tRNA synthetase (ProRS), but not for human ProRS. To further delineate species-specific differences in acceptor stem recognition, atomic group mutagenesis was used to probe the role of sugar–phosphate backbone interactions in recognition of human tRNA(Pro). Incorporation of site-specific 2′-deoxynucleotides, as well as phosphorothioate and methylphosphonate modifications within the tRNA acceptor stem revealed an extensive network of interactions with specific functional groups proximal to the first base pair and the discriminator base. Backbone functional groups located at the base of the acceptor stem, especially the 2′-hydroxyl of A66, are also critical for aminoacylation catalytic efficiency by human ProRS. Therefore, in contrast to the bacterial system, backbone-specific interactions contribute significantly more to tRNA recognition by the human enzyme than base-specific interactions. Taken together with previous studies, these data show that ProRS-tRNA acceptor stem interactions have co-adapted through evolution from a mechanism involving ‘direct readout’ of nucleotide bases to one relying primarily on backbone-specific ‘indirect readout’.